Symptomatic Tarlov Cyst – Case Report and Review of the Literature - Md Nasir Uddin; Nafees Imtiaz Ahmed; Muhammad Nazmul Baqui; Md Anisul Islam Khan (Bangladesh Journal of Neurosurgery, 2024)
Here we describe the case of a 53 year old woman presenting with low back pain with radiation was diagnosed with sacral bilateral Tarlov cyst. She was treated by laminectomy, disintegration of cyst and duroplasty. Histopathological examination of the cyst wall was confirmed the diagnosis. Symptomatic Tarlov cysts are extremely rare, commonly presenting as sacral or lumbar pain syndromes, sciatica or rarely as cauda equina syndrome. Tarlov cysts should be considered in the differential diagnosis of patients presenting with these complaints. Bang. J Neurosurgery 2023; 12(2):125-128